2021
DOI: 10.1109/tvcg.2021.3106504
|View full text |Cite
|
Sign up to set email alerts
|

Understanding, Modeling and Simulating Unintended Positional Drift during Repetitive Steering Navigation Tasks in Virtual Reality

Abstract: Virtual steering techniques enable users to navigate in larger Virtual Environments (VEs) than the physical workspace available. Even though these techniques do not require physical movement of the users (e.g. using a joystick and the head orientation to steer towards a virtual direction), recent work observed that users might unintentionally move in the physical workspace while navigating, resulting in Unintended Positional Drift (UPD). This phenomenon can be a safety issue since users may unintentionally rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…We could imagine that those paradigms could be used for other types of techniques that requires the use of virtual translation such as steering techniques. A recent research work showed that users tend to drift in the workspace while using steering techniques, reaching the boundaries of the workspace even though those techniques do not require physical translational movements [Brument et al 2021]. Thus, the use of rotation gains during virtual translation could be interesting to manipulate users' movements and try to maintain them at the center of the workspace while navigating in the VE.…”
Section: Towards User-centered Gainmentioning
confidence: 99%
“…We could imagine that those paradigms could be used for other types of techniques that requires the use of virtual translation such as steering techniques. A recent research work showed that users tend to drift in the workspace while using steering techniques, reaching the boundaries of the workspace even though those techniques do not require physical translational movements [Brument et al 2021]. Thus, the use of rotation gains during virtual translation could be interesting to manipulate users' movements and try to maintain them at the center of the workspace while navigating in the VE.…”
Section: Towards User-centered Gainmentioning
confidence: 99%
“…In addition, compared to traditional paper-and-pencil tests, VR-based goal-directed navigation and recognition tasks are performed by immersing patients in a 3D virtual environment (La Corte et al, 2019 ). VR navigation tasks may involve more complex processes, including representational updating, spatial memory, and adaptation of the self when approaching a distant spatial target (Brument et al, 2021 ). These skills and manipulations cannot be accounted for in paper-and-pencil tests.…”
Section: Introductionmentioning
confidence: 99%
“…Unintended Positional Drift can also appear during steering navigation in virtual environments. Brument et al analyzed and modelled UPD based on the movement of the users while performing a slalom task using virtual steering techniques (Brument et al, 2021). The modelling of the UPD is used to reproduce the same task in a simulation framework and to understand why and how the UPD appears.…”
Section: Redirected Walking-in-placementioning
confidence: 99%